The Relative Importance Of Cash Flow News And Discount Rate News At Driving Stock Price Change - Mohsen Jafarian; Izani Ibrahim; Fauzias Mat Nor (Malaysian Finance Association, 2024)
Capital Markets Review Vol. 26, No. 1, pp. 56-72 (2018)